TRANSFUSION STRATEGY IN THE SETTING OF ACUTE UPPER GASTROINTESTINAL (GI) HAEMORRHAGE: CLINICAL IMPORTANCE AND EXTENT OF THE EVIDENCE, FUTURE SOLUTIONS - Kebkalo, A.; Tryliskyy, Y.; Kluzko, І.; Karpenko, О.; Sykorskiy, N. (World of Medicine and Biology, 2016)
Acute upper gastrointestinal (GI) haemorrhage is one of the most common GI emergencies. It is associated with substantial morbidity and mortality, as well as economic cost. Blood transfusion is a prominent element in clinical management of gastrointestinal (GI) bleeding. Although the issue is of superior importance, clear evidence-based algorithms of packed red blood cells (PRBC) transfusion are absent. This review summarizes and critically appraises the most recent major published studies on the issue of PRBC transfusion in the setting of GI haemorrhage. Comparative analysis of national guidelines of developed English-speaking countries and Ukraine is also provided.
Keywords: haemotrasfusion; packed red blood cells; gastrointestinal bleeding